Enhancing sustainable performance among manufacturing SMEs: the interplay of knowledge management and organizational structure - Ibraheem Saleh Al Koliby; Nurul Hidayana Mohd Noor; Abdullah Kaid Al-Swidi; Mohammed A. Al-Hakimi; Nurul Aini Binti Mehat (Discover Sustainability)
Abstract Manufacturing SMEs face persistent challenges in achieving sustainable performance (SP) due to resource constraints and ineffective knowledge management (KM) practices. Drawing on the knowledge-based view, contingency theory, and the triple bottom line framework, this research investigates the influence of KM on SP in Malaysian manufacturing SMEs, under the moderating effect of organizational structure (OS). Data was gathered through a survey of 428 SMEs, yielding 122 valid responses, and analyzed utilising structural equation modeling. The results confirm that KM significantly enhances SP, while OS plays a crucial role in strengthening this relationship. These findings offer both theoretical and practical contributions by demonstrating how adaptive organizational structures can amplify the benefits of KM, enabling SMEs to build resilience and drive sustainable growth. Decision-makers in government and industry can use these insights to optimize resource allocation and implement strategies that generate long-term economic, social, and environmental value. Future research should explore the longitudinal effects of KM on SP across various industries to enhance the applicability of these findings.